Hinge Flap with Triangular Extension for Reconstruction of Pharyngocutaneous and Laryngocutaneous Fistulas. Issue 1 (January 2018) - Azuma, Ryuichi; Aoki, Shimpo; Kuwabara, Masahiro; Aizawa, Tetsushi; Nagano, Hisato; Kiyosawa, Tomoharu
Abstract : Summary: Hinge flaps are commonly used for closure of a pharyngocutaneous fistula (PCF) or laryngocutaneous fistula. These flaps are employed to augment the wall of the pharynx or larynx, but the junction between the reconstructed and native lumens can eventually become narrow and irregular after reconstruction with standard hinge flaps. We devised a method of adding a triangular extension to the end of either or both flaps and used it to treat 3 patients. In 1 patient who developed a PCF (4 × 10 cm) after laryngectomy followed by radiotherapy, the fistula was closed with 2 hinge flaps. One flap had a caudal triangular extension. The residual skin defect was covered by a pedicled latissimus dorsi musculocutaneous flap. Another patient who developed a PCF (2.5 × 3 cm) after laryngectomy underwent 2-stage reconstruction using a buccal mucosal graft with a triangular extension, followed by 2 hinge flaps. A patient who developed an laryngocutaneous fistula (1 × 2 cm) after radiotherapy and subsequent partial laryngectomy underwent reconstruction using 2 hinge flaps, each of which had a triangular extension. The skin defect was covered by another flap. Postoperative CT or video fluoroscopic examination of swallowing showed a smooth lumen with no strictures in all 3 patients. The triangular extension of the hinge flap supplements the pharyngeal/laryngeal wall at the junction between the reconstructed and intact regions, thus avoiding postoperative stricture. Especially with PCF reconstruction, restoration of a smooth luminal surface minimizes dysphagia. Abstract : Supplemental Digital Content is available in the text.